2017
DOI: 10.1371/journal.pone.0177919
|View full text |Cite
|
Sign up to set email alerts
|

ERBB3: A potential serum biomarker for early detection and therapeutic target for devil facial tumour 1 (DFT1)

Abstract: Devil Facial Tumour 1 (DFT1) is one of two transmissible neoplasms of Tasmanian devils (Sarcophilus harrisii) predominantly affecting their facial regions. DFT1’s cellular origin is that of Schwann cell lineage where lesions are evident macroscopically late in the disease. Conversely, the pre-clinical timeframe from cellular transmission to appearance of DFT1 remains uncertain demonstrating the importance of an effective pre-clinical biomarker. We show that ERBB3, a marker expressed normally by the developing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 205 publications
0
10
0
Order By: Relevance
“…Interestingly, both PDGFA and PDGFB , encoding ligands for PDGFRs, have undergone copy number gains in DFT1 (and PDGFA is additionally involved in a SV in DFT1 [ Murchison et al., 2012 ; Tables S4 and S5 ]). Furthermore, ERBB3 showed copy number gains in DFT1 and is expressed in DFT1 ( Hayes et al., 2017 , Taylor et al., 2017 ), and a subset of DFT1s carried gains of NRG2 , encoding an ERBB ligand ( Figure 4 B; Tables S3 and S4 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, both PDGFA and PDGFB , encoding ligands for PDGFRs, have undergone copy number gains in DFT1 (and PDGFA is additionally involved in a SV in DFT1 [ Murchison et al., 2012 ; Tables S4 and S5 ]). Furthermore, ERBB3 showed copy number gains in DFT1 and is expressed in DFT1 ( Hayes et al., 2017 , Taylor et al., 2017 ), and a subset of DFT1s carried gains of NRG2 , encoding an ERBB ligand ( Figure 4 B; Tables S3 and S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…Tissues were orientated on the EG1160 (Leica Microsystems), embedded in paraffin wax (Leica Microsystems) and sectioned at 3 microns using a Leica RM2245 microtome and adhered to microscope slides (Menzel Gläser, Thermo Fisher Scientific) for 20 min at 60°C. Sections were deparaffinized, rehydrated and stained using Jung autostainer XL (Leica Microsystems) for Hematoxylin (Australian Biostain) and Eosin, dehydrated, cleared, cover slipped (Leica Microsystems) and mounted in CV Mount (Leica Microsystems) ( Hayes et al., 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…The underlying mechanism of maintained STAT3 activation and the apparent lack of negative regulation requires further investigation. Mutually not exclusive, the involved processes may include recently detected copy gains of ERBB3 (Hayes et al, 2017; Taylor et al, 2017) leading to enhanced ERBB2-ERBB3 heterodimer activity, the secretion of ligands of the ERBB family, blunted negative control by phosphatases or the SOCS-ubiquitin pathway ( Fig. S5 ).…”
Section: Discussionmentioning
confidence: 99%
“…NF2, ErbB3 and downstream effectors PI3K-Akt or MAPK signalling pathways are therefore prime candidates for future immunohistochemistry and functional studies to determine if they are involved in DFT1 tumourigenesis. It has recently been shown that elevated levels of ErbB3 are detectable in devil sera several months prior to visual tumour eruptions 34 making it imperative that the pathway involving NF2 and ErbB3 be prioritised for further investigation. Additionally, germline mutations in the tumour suppressor LZTR1 are associated with a predisposition for an inherited disorder responsible for the development of multiple schwannomas in humans 35 , making the entire NF2 region a high priority for further investigation.…”
Section: Discussionmentioning
confidence: 99%